The Assessment of Alchornea Cordifolia Activity in Aflatoxicosis Reduction in Rat. - Aholia Jean- Baptiste Adépo; Pierre Manda; Jean Verdier Ngbé; Aïssata Diakité; Tigori Béatrice Sangaré; Djédjé Sébastien Dano (Journal of Antioxidant Activity, 2017)
Introduction: Aflatoxins are cytotoxic andserve as one of the key risk factors of hepatocellular carcinoma. Currently, plants and extract are widely used as potential scavenging substances for the detoxification of mycotoxins. Thus, this study aims to investigate the activity of the crude ethanolic leaves extract from Alchorneacordifolia in aflatoxicosis prevention. Material and Methods: The phytochemical screening was performed through qualitative analysis based on coloring and/or precipitation reactions. Groups of rats were treated daily with a mixture dose of aflatoxin B1 (AFB1) at 150 µg/kg and the crude extract of Alchorneacordifolia at doses of 50, 100, and 300 mg/kg for 21 days. The body weight, biochemical, and histological assessments were determined. Results: The phytochemical screening revealed the presence of polyphenols, flavonoids, sterols and terpenoids, quinoid compounds, tannins catechic and alkaloids. AFB1 treatmentcaused a significant increase of transaminases, urea, and creatinine abundances but reduced the rates of albumin and total proteins. Alchorneacordifolia administration alleviated biochemical parameters and body weight gain compared with the AFB1 group (p<0.05). The histological lesions of organs (liver and kidney) caused by AFB1 were significantly improved after administration of the extract at a dose of 300 mg/kg. Conclusion: This plant plays a beneficial role in AFB1-induced injury and may be used in the treatment of aflatoxicosis.
Keywords: phytochemical screening